y=mx+b
since the b is 0, the formula is y= -3x
Answer:
Step-by-step explanation:
<u>Property of the odd function is:</u>
<u>Same applies to the given function:</u>
- f(x) = -2x⁵ + x³ - 7x
- f(- x) = -2(-x)⁵ + (- x)³ - 7(-x) = 2x⁵ - x³ + 7x = - (2x⁵ + x³ - 7x) = - f(x)
Answer:
60.1
Step-by-step explanation:
Just get 72.60 and subtract 12.50
Answer:
7
Step-by-step explanation:
can you mark me brainliest
Divide the sides of the larger triangle by the corresponding side of the smaller one:
18/7.2 = 2.5
Figure A is 2.5 times the size of figure B
The scale factor is 2.5